Applying Black’s Theory of Law to Juvenile Justice Decisions - Chappell, Allison T. (American journal of criminal justice, 2021)
An abundance of research has examined the impact of legal and extra-legal variables on juvenile justice processing. Much of this research, whether explicitly or implicitly, investigates the extent to which extra-legal variables, such as race, ethnicity, and gender, impact decision making. Some of these studies have also considered how social situational factors shape outcomes. However, there remains a need for theoretical development to improve our understanding of how the social structure of a case influences processing. Informed by an interpretation of Black’s theory of law, the current study investigated the influence of family structure, school performance, prosocial activities, and demographic variables on intake and adjudication decisions in delinquency cases in a mid-Atlantic state. Overall, we found moderate support for Black’s theory. Findings suggested that race, gender, and age consistently conditioned juvenile justice processing, but that social situational variables had inconsistent effects on intake and adjudication. Implications for theory, policy, and practice are discussed.